The prophets speak on forced migration - Boda, Mark J.; Ames, Frank Ritchel; Ahn, John J.; Leuchter, Mark (2015)
"In this collection of essays dealing with the prophetic material in the Hebrew Bible, scholars explore the motifs, effects, and role of forced migration on prophetic literature. Students and scholars interested in current, thorough approaches to the issues and problems associated with the study of geographical displacement, social identity ethics, trauma studies, theological diversification, hermeneutical strategies in relation to the memory, and the effects of various exilic conditions will find a valuable resource with productive avenues for inquiry"--
Includes bibliographical references (pages 181-204) and index.
Keywords: Bible. -- Criticism, interpretation, etc; Forced migration